Climate change 2014 : impacts, adaptation, and vulnerability : Working Group II contribution to the fifth assessment report of the Intergovernmental Panel on Climate Change. Part A, Global and sectoral aspects - Field, Christopher B. (Cambridge : Cambridge University Press, 2014)
This latest Fifth Assessment Report of the Intergovernmental Panel on Climate Change (IPCC) will again form the standard reference for all those concerned with climate change and its consequences, including students, researchers and policy makers in environmental science, meteorology, climatology, biology, ecology, atmospheric chemistry and environmental policy.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Climatic changes; Global environmental change; Climatic changes -- Government policy; Climatic changes -- International cooperation